SALARY ASPECTS AND SOCIAL BENEFITS OF A GROUP OF COLLABORATORS FROM HIGHER EDUCATION INSTITUTIONS (HEI) IN VILLAVICENCIO - COLOMBIA - Author (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Higher Education Institutions (HEI) face situations that require their continuous improvement, with respect to the quality of their educational programs and having a suitable staff that takes them to these standards. In addition to the teachers, the rest of the HEI collaborators must have some minimum aspects that lead them to have motivation within the organization. This study has been carried out with the purpose of analyzing the salary and well-being aspects of HEI collaborators in Villavicencio-Colombia. This cross-sectional and descriptive research was conducted in 2019. A random group of 165 people contributed to the study. A questionnaire was used for data collection, which included personal, work, and organizational attributes, regarding wages and well-being. Data were collected over a two-month period, the Statistical Package for Social Sciences (SPSS v25) was used, and descriptive statistical tests were used for the analysis. According to themand descriptive statistical tests were used for the analysis. According to the results, women predominate and a large number of collaborators are professionals, mostly with a postgraduate degree, very few perceive the application of the emotional salary. Training is the most applied social benefit, in the manager category men receive up to 2.8 times more salary than women and a positive relationship was found between salary and experience.